Government-made house price bubbles? Austerity, homeownership, rental, and credit liberalization policies and the "irrational exuberance" on housing markets - Konstantin Kholodilin; Sebastian Kohl; Florian Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Housing bubbles and crashes are catastrophic events for economies, implying enormous destruction of housing wealth, financial default risks, construction unemployment, and business cycle downturns. This paper investigates whether governmental housing policies can affect economies' propensity to build up speculative house price bubbles. Specifically, we focus on the liberalization effects of rent and credit regulation as well as homeownership and austerity policies. Drawing on a long-run time series from 16 countries since 1870, we identify speculative price bubbles through explosive root tests, corroborated by a narrative approach. Estimating logit models, we find that tighter rent and credit controls make bubbles less likely to emerge by dampening price increases, while certain homeownership and tenant subsidies and government austerity increase the likelihood of bubbles. The paper illustrates the logic of rent, credit, homeownership and austerity effects with two case studies.
Keywords: C43; O18; R38; 330; speculative house price bubbles; rent control; homeowner taxation; explosive roots; panel data logit model